1995
DOI: 10.1016/1074-7613(95)90120-5
|View full text |Cite
|
Sign up to set email alerts
|

Potent effects of low levels of MHC class II-associated invariant chain on CD4+ T cell development

Abstract: Invariant chain (Ii)-negative mice exhibit defects in MHC class II assembly and transport that results in reduced levels of surface class II, altered antigen presentation, and inefficient positive selection of CD4+ T cells. Many CD4+ T cells that do mature in Ii-negative mice express a cell surface phenotype consistent with aberrant positive selection or peripheral activation. Reconstitution of these mice with low levels of either the p31 or p41 form of Ii does not restore transport of the bulk of class II or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 92 publications
1
33
1
Order By: Relevance
“…CD44v9, although increased in prostate cancer cells (36), was not increased at the cell surface. Taken together, these data suggest that although CD44 may be necessary for CD74 signaling (21,22), it is not a regulating mechanism because it is present in overabundance and in steady-state levels at the cell surface. Therefore, these results suggest that up-regulation of cell surface CD74 is the necessary step in mediating MIF-CD74-activated signal transduction.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…CD44v9, although increased in prostate cancer cells (36), was not increased at the cell surface. Taken together, these data suggest that although CD44 may be necessary for CD74 signaling (21,22), it is not a regulating mechanism because it is present in overabundance and in steady-state levels at the cell surface. Therefore, these results suggest that up-regulation of cell surface CD74 is the necessary step in mediating MIF-CD74-activated signal transduction.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have identified recruitment of transmembrane CD44 as a potential accessory protein required for MIF-CD74 signal transduction (21,22). In addition, we recently showed the formation of a molecular complex between MIF, CD74, and CD44 in HT-1376 bladder carcinoma cells (23).…”
mentioning
confidence: 98%
“…The intracytoplasmic portion of CD74 is known to undergo phosphorylation (Ser6, Ser8), in a protein-kinase dependent manner, but evidence supporting ligand activation in this process has not been reported [54]. It nevertheless is noteworthy that recent studies have identified an accessory role for CD74 in T cell stimulation, and by a function that requires a chondroitin-sulphatedependent interaction between CD74 and CD44 [33,34]. CD44 is a widely-expressed, polymorphic transmembrane protein with known tyrosine kinase activation properties [55].…”
Section: How Does Mif Mediate Signal Transduction Through Its Receptor?mentioning
confidence: 99%
“…We sequenced 50 clones and found that the majority encoded CD74, the cell surface form of the Major Histocompatibility Class II-associated invariant chain, that is a 31-41 kDa Type II transmembrane protein (Figure 3). Invariant chain has been well-studied for its role as a Major Histocompatibility Class II chaperone [32], and the cell surface CD74 form has a previously described role in immune cell co-stimulation [33,34]. It is notable that like MIF, cell surface CD74 is expressed as a homotrimer [35].…”
Section: Cloning Of the Mif Receptormentioning
confidence: 99%
“…In some cases, immunoprecipitates were incubated with endoglycosidase H or N-glycosidase (Roche Applied Science, Indianapolis, IN) as described (39). Western blotting was performed as previously described (40). Blots were incubated with appropriate dilutions of primary Abs, followed by incubation with HRP-conjugated secondary Abs (Amersham Biosciences).…”
Section: Radiolabeling Immunoprecipitation and Western Blotsmentioning
confidence: 99%